Marina and John Bear: NOT Your Mother’s Cookbook - Davidson, Alan (Petits Propos Culinaires, 2024)
Marina and John Bear: NOT Your Mother’s Cookbook: SLG Books, Berkeley, 2002: ISBN 0-943389-00-0: 208 pp, b/w illus., p/b, $16.95.